PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS, PROFITABILITAS DAN PRODUK DOMESTIK BRUTO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI - Trirahaju, Justina (Jurnal Riset Keuangan dan Akuntansi, 2015)
This research is a quantitative research that aims to analyze factors influencing the profit growth at textile and garmen company listed in Indonesia Stock Exchange, that are liquidity ratio that measured by current asset, solvability ratio that measured by DER, activity ratio that measured by TATO, profitability ratio that measured by NPM and Gross Domestic Product. Population in this research is all of textile and garmen companies that listing in BEI. Implementing the purposive sampling so got 13 researches that analyzed by panel data regression with Ordinary Least Square (OLS) model. The result shows that liquidity ratio influences positively towards profit growth, solvability ratio doesn’t influence towards profit growth, activity ratio doesn’t influence towards profit growth, profitability ratio influences positively towards profit growth, and gross domestic product doesn’t influence towards profit growth at textile and garmen companies listed in Indonesia Stock Exchange.Based on the analysis in this study, the following suggestions are presented: (1) For further research may add other independent variables that predict the effect on profit growth and increase the number of observations in order to get better a study and research users can obtain more information, to increase the number of observation studies, the researchers can then immediately take the primary data to each company so that the collected data would be coming more and research results would be better, further research can be carried out by expanding the study area is not only the textile and garment company, but also all companies listed on the Indonesia Stock Exchange, (2) For the company to be concerned about the condition of the company's profit growth is still fluctuate every year and this proves that there is still a lack of consistency in maintaining the company's profit trend continues to rise. So it needs to be reviewed on the causes of fluctuations in profit growth.